Cold versus Warm Tumescent Solution in Arm Liposculpture: A Double-Blind Randomized Clinical Study - Laura C. Cala Uribe; Mauricio E. Perez Pachon; Andreina Zannin Ferrero (Plastic & Reconstructive Surgery, 2026)
Background: Use of cold tumescent solutions in liposuction is hypothesized to enhance vasoconstriction, potentially reducing bleeding and improving clinical outcomes. However, evidence for its efficacy in arm liposculpture remains inconclusive. The authors compare the effects of cold (4°C) and warm (37°C) tumescent solutions on postoperative outcomes in arm liposculpture, focusing on pain, bruising, and fat emulsification quality. Methods: This double-blind, randomized clinical trial enrolled patients undergoing bilateral arm liposculpture. One arm was infiltrated with a cold tumescent solution and the other with a warm solution, randomly assigned. Liposuction was performed using vibration amplification of sound energy at resonance (VASER)-assisted fat emulsification followed by power-assisted liposuction or conventional suction-assisted liposuction. Outcomes included pain (visual analog scale) assessed at days 1, 8, 15, and 30; bruising; and lipocrit values. Results: A total of 104 arms were analyzed from 52 female participants (mean age, 39.7 years; mean body mass index, 24.7 kg/m 2 ). Pain scores were similar between groups at all time points (day 1: cold = 5 [2 to 9]; warm = 6 [2 to 9]; P = 0.9). Bruising areas were comparable (cold, 40,444 mm 2 ; warm, 41,212 mm 2 ; P > 0.05). Lipocrit values for power-assisted liposuction (MicroAire) and suction-assisted liposuction techniques showed no significant differences ( P > 0.05). Patients reported high satisfaction, with 78.7% of patients reporting being “very satisfied” and 96.1% recommending the procedure. Conclusions: Cold tumescent solutions do not significantly enhance outcomes in arm liposculpture compared with warm solutions. Surgeons should exercise caution with cold solutions due to potential hypothermia risks. Further research is warranted to assess the potential long-term effects of cold tumescent infiltration.